Analisis Dampak Transformasi Digital Perbankan Terhadap Inklusi Keuangan dan Kinerja UMKM di Provinsi Sumatera Utara - Santhos Frananda; Lia Nazliana Nasution; Rusiadi (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to determine the influence of digital banking transformation on the performance of MSMEs in North Sumatra Province which is moderated by financial inclusion. This type of research is quantitative research. The sampling technique used is a non-probability sampling technique with a purposive sampling approach so that the determination of the number of samples refers to the needs of SEM-PLS analysis, so the sample used in this study was ± 250 respondents. The data analysis technique used was Partial Least Square (Smart-PLS) with data analysis, namely the measurement model test (outer model) and the structural model test (inner model). The results of the study show that: (1) Financial Inclusion has a positive and significant effect on MSME Performance. (2) Banking Digital Transformation has a significant effect on MSME Performance. And (3) Financial Inclusion significantly moderates the relationship between Banking Digital Transformation on MSME Performance